Corruption in sport: From the playing field to the field of policy. Issue 2 (1st June 2015) - Masters, Adam
Abstract: How is corruption in sport evolving into a global public policy issue? In the past century, four trends have affected sport according to Paoli and Donati (2013) — de-amateurisation at the turn of the twentieth century, medicalisation since the 1960s, politicisation and commercialisation to the point where sport is now a business worth more than US141 billion annually. Each of these trends had a corrupting effect on what is generally perceived as a past 'golden age' of sport. In the twenty-first century more public funding is being directed into sport in the developed and developing world. As a result this paper will argue organised sport has entered a fifth evolutionary trend — criminalisation. In this latest phase, public policy needs to grapple with what constitutes corruption in what has historically been a private market.